2021
DOI: 10.3390/ijms22136719
|View full text |Cite
|
Sign up to set email alerts
|

eNAMPT Is Localised to Areas of Cartilage Damage in Patients with Hip Osteoarthritis and Promotes Cartilage Catabolism and Inflammation

Abstract: Obesity increases the risk of hip osteoarthritis (OA). Recent studies have shown that adipokine extracellular nicotinamide phosphoribosyltransferase (eNAMPT or visfatin) induces the production of IL-6 and matrix metalloproteases (MMPs) in chondrocytes, suggesting it may promote articular cartilage degradation. However, neither the functional effects of extracellular visfatin on human articular cartilage tissue, nor its expression in the joint of hip OA patients of varying BMI, have been reported. Hip OA joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Importantly, in the OA joint, we have reported that obesity imprints an inflammatory activated synovial fibroblast phenotype, with fibroblasts from obese OA patients being more proliferative and secreting greater amounts of IL-6 [ 13 , 14 ]. Importantly, obesity is a major risk factor for the development of OA in both weight-bearing joints such as the knee [ 22 , 23 ] and hip [ 24 ], as well as non-weight bearing joints such as the hand [ 25 ], promoting cartilage degeneration [ 26 ] and sclerotic subchondral bone pathology [ 27 ]. Therefore, understanding whether metabolic differences underpin this obese inflammatory activated OA synovial fibroblasts could provide a new rationale for targeting synovial joint inflammation in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in the OA joint, we have reported that obesity imprints an inflammatory activated synovial fibroblast phenotype, with fibroblasts from obese OA patients being more proliferative and secreting greater amounts of IL-6 [ 13 , 14 ]. Importantly, obesity is a major risk factor for the development of OA in both weight-bearing joints such as the knee [ 22 , 23 ] and hip [ 24 ], as well as non-weight bearing joints such as the hand [ 25 ], promoting cartilage degeneration [ 26 ] and sclerotic subchondral bone pathology [ 27 ]. Therefore, understanding whether metabolic differences underpin this obese inflammatory activated OA synovial fibroblasts could provide a new rationale for targeting synovial joint inflammation in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several adipokines have shown similar effects in joint diseases. For instance, resistin increases CCL2 expression in osteoarthritis (OA) synovial broblasts (31), while visfatin and adiponectin upregulate levels of several chemokines in OA and RA (32,33). Thus, our evidence showing that nesfatin-1 induces increases in CCL2 expression provides a new insight into adipokine involvement in joint disease.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, several adipokines have shown similar effects in joint diseases. For instance, resistin increases CCL2 expression in osteoarthritis (OA) synovial fibroblasts 36 , while visfatin and adiponectin upregulate levels of several chemokines in OA and RA 37 , 38 . Thus, our evidence showing that nesfatin-1 induces increases in CCL2 expression provides a new insight into adipokine involvement in joint disease.…”
Section: Discussionmentioning
confidence: 99%